A comparison of the cooperative method of teaching filing with the traditional textbook method - Shotwell, Herbert D., author; Aiken, D. W., advisor; Heilig, Herb, committee member; Britton, Russell K., committee member; Johnson, Howard L., committee member; Chandler, E. P., committee member (Colorado State University. Libraries, 1946)
To view the abstract, please see the full text of the document.
Keywords: Filing systems; Filing systems -- Study and teaching